Palestinian Resistance Narratives in the Poetry of Ayman al-Atoom: A Critical Analysis of Literary Aesthetics and Political Consciousness - Aida Hayati Mohd Sanadi; Nursafira Lubis Safian; Nurul Iman Mohamad Anuar Kamal; Faiz Hadi (Ijaz Arabi Journal of Arabic Learning, 2026)
Palestinian resistance represents one of the central themes in contemporary Arab literature, where poetry serves as a powerful medium for articulating the hardships, hopes and defiance of an oppressed and displaced people. Ayman al-Atoom stands among the notable contemporary Arab poets whose works vividly expose the social and political realities of the Arab world. This study offers a critical analysis of Palestinian resistance narratives in selected poems of the Jordanian poet, examining both their literary aesthetics and political consciousness. Employing descriptive and analytical methods, the research explores how al-Atoom’s poetic language, imagery and symbolism construct a discourse of resistance. The findings reveal that his poetry functions as a reflective mirror of the Palestinian experience, highlighting themes of pain, suffering, tragedy, resilience and revolution. Moreover, the study underscores the poet’s view that the liberation of Palestine is a collective responsibility of the entire Muslim ummah, presenting the Palestinian cause not merely as a regional or national concern, but as a universal human tragedy. The study concludes that al-Atoom’s integration of aesthetic expression and political awareness contributes significantly to contemporary resistance literature and enriches the understanding of Palestine’s ongoing struggle.